Optimizing Ammonia Adsorption Using Activated Carbon from Tamarind Pulp - Na-Lampang, Chaiyawat; Assawasaengrat, Pornsawan; Phumjan, Lamphung; Narkrugsa, Woatthichai; Sriprom, Pongsert (My University, 2021)
Ammonia is an essential waste from fish and shrimp which has an effect on fish and shrimp transportation for export. This study aimed to remove ammonia by Activated Carbon adsorption. The activated carbon was prepared from Tamarind pulp using different methods (NaOH, H2SO4, the hydrothermal technique and activated by H2SO4 and H2SO4 hydrothermal followed by NaOH). The Activated Carbon was characterized by and Iodine number and Fourier Transform I nfrared Spectroscopy (FT-IR). The results showed that the iodine number of activated carbon prepared by the hydrothermal technique and activated by H2SO4 have the highest surface area and porosity at 537 mg/g, and the functional group on activated carbon surface is carbonyl and sulfonyl group. For ammonia adsorption, the experiments were designed by Box-Behnken design at 3 factors 3 levels including Contact time (10, 95 and 180 min), Dosage of activated carbon (0.5, 1.25 and 2.0 g) and pH of the solution (2, 6.5 and 11). The concentration of ammonia was determined by UV-Visible spectrophotometer. The result showed that the main effects and the interaction effects were found significant effect on ammonia adsorption at confidence level of 95%. However, the interaction effects between contact time and activated carbon dosage was insignificant. Finally, the optimized results suggested that 48.32 ± 0.82% of ammonia concentration could be removed by activated carbon from tamarind pulp under the following conditions: PH of 11, a contact time of 95 min, and activated carbon dosage of 2 g/100 mL. The results are believed to be of importance to fish and shrimp transportation for reduced ammonia and other similar applications.
Keywords: Activated Carbon; Ammonia adsorption; Chemical activation; Hydrothermal; Tamarind pulp